The Paths from Middle Class: Evaluation of the Poverty Risks for the Russian Middle Class - Pishnyak, Alina; Khalina, Natalia; Nazarbaeva, Elena (Экономическая социология, 2023)
The middle class is usually perceived as a main supporter of innovations, source of political stability, and core consumer of goods and services. As a result, its members are traditionally supposed to have high human potential and make a significant contribution to economic growth both in certain country and all over the world, which permanently generates great interest in the issues concerning middle class. However, the main research questions have changed significantly over the last years. The experts both in Russia and abroad highlight the factors that negatively influence the position of the middle class. These are changes in labor market, price growth that outruns the growth of income, increase of tax burden and problems with access to public goods. During COVID-19 pandemic the income has fallen, the risks of unemployment have increased, and the costs of healthcare also have grown. The scholars in different countries underline similar tendencies: middle-class members, who already had to live in an ambiguous world, faced the risks of falling into poverty during the corona crisis. Using data from the Russian Longitudinal Monitor Survey, we evaluate the tracks of middle-class families during 2014-2020 and demonstrate that the problem of poverty affects a part of this social stratum every year. But the share of middleclass members with the income below the poverty line is relatively low and remains largely unaffected by the current corona crisis.